Analysis of basic characteristics for linear oscillatory actuator - Misron, Norhisam; Abdul Shukor , Fairul Azhar; Khamis, Alias; Hizam , Hashim; Mariun , Norman; Jelani, Abdul Razak (2007)
Linear oscillatory actuator (LOA) is an actuator that produces linear motion. It convert electrical energy to mechanical energy. The oscillatory effect of linear motion can be occurs when the movement is repeated to and forth periodically. This can be achieved when AC voltage is supply to the LOA. LOA has become one of the most popular actuator used in industry especially in office automation and factory automation. Its have a compact and simple structure and easy to control compare to rotational motor. The advantages of linear actuator are small size, low power and high thrust. This LOA had been designed and developed successfully and paper is present to study the basic characteristics of LOA. Basic characteristics need to be studied in this paper are including frequency characteristics, vibration and displacement characteristics and thrust characteristics. These characteristics can be use to find suitable element in order to upgrade the performance of LOA beside use to design and develop the electric generation for LOA.